2018
DOI: 10.21470/1678-9741-2018-0137
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Effect of Mean Perfusion Pressure on the Development of Acute Kidney Injury after Transcatheter Aortic Valve Implantation

Abstract: ObjectiveTo evaluate the predictive value of mean perfusion pressure (mPP) in the development of acute kidney injury (AKIN) after transcatheter aortic valve implantation (TAVI).MethodsOne hundred and forty seven consecutive patients with aortic stenosis (AS) were evaluated for this study and 133 of them were included. Mean arterial pressure (mAP) and central venous pressure (CVP) were used to calculate mPP before TAVI procedure (mPP = mAP-CVP). The occurrence of AKIN was evaluated with AKIN classification acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Greater relative hypotension was caused by higher preoperative or lower postoperative MPP, while smaller relative hypotension was caused by lower preoperative or higher postoperative MPP. Since previous studies [ 16 , 17 , 38 ] and our study have consistently shown that lower postoperative MPP is a risk factor of AKI, the non-linear relationship between preoperative MPP and AKI progression could weaken the association between relative hypotension and AKI progression. Higher preoperative MPP could increase the risk of AKI due to the right shift in the lower pressure limit of renal autoregulation in the presence of chronic hypertension [ 14 ].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Greater relative hypotension was caused by higher preoperative or lower postoperative MPP, while smaller relative hypotension was caused by lower preoperative or higher postoperative MPP. Since previous studies [ 16 , 17 , 38 ] and our study have consistently shown that lower postoperative MPP is a risk factor of AKI, the non-linear relationship between preoperative MPP and AKI progression could weaken the association between relative hypotension and AKI progression. Higher preoperative MPP could increase the risk of AKI due to the right shift in the lower pressure limit of renal autoregulation in the presence of chronic hypertension [ 14 ].…”
Section: Discussionmentioning
confidence: 55%
“…Mean perfusion pressure (MPP), which is the difference between MAP and central venous pressure (CVP), can also be used as a surrogate marker for renal perfusion because elevated CVP has been reported as a risk factor for AKI in ICU patients [ 13 , 14 ]. Although CVP monitoring is readily available in patients after cardiac surgery [ 15 ], few studies have assessed the relationship between MPP and AKI in this population [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies, including a recent meta-analysis [4] [5], have suggested that the mechanism underlying AKI in this specific patient population is not necessarily related to contrast-induced nephropathy (CIN), but rather to other elements which may affect renal perfusion including baseline comorbidities, procedure-related and periprocedural factors. A number of studies have focused on the predictors of AKI after TAVI [5] [6] [7] [8] [9] [10] [11] [12], but less work has been carried regarding the effects of contrast medium (CM) amount and osmolality [13].…”
Section: Introductionmentioning
confidence: 99%
“…And for patients undergoing cardiac surgery, they presented with decreased perfusion pressure characterized by renal venous congestion [ 39 ]. The correlation between absolute level of MPP and the deterioration of renal function may be more significant [ 40 ]. After adjusting for TWA-MPP, the correlation between MPPV and the deterioration of renal function weakened.…”
Section: Discussionmentioning
confidence: 99%